PENGARUH NET PROFIT MARGIN (NPM) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR PERDAGANGAN RITEL DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Syabila, Tiara; Sawukir (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Net Profit Margin (NPM) and Earning Per Share (EPS) on stock prices in retail trade subsector companies on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The type of research used in this research is quantitative research with descriptive methods. The population used was 29 retail trade subsector companies on the Indonesia Stock Exchange, with a sample of 9 (nine) companies that fulfilled the sample selection criteria. The analysis techniques used in this study are descriptive statistics, model selection test, classical assumption test, panel data regression test, and hypothesis testing. Based on the research results, the Net Profit Margin (NPM) variable partially has no effect on stock prices, as evidenced by the t-statistic value of 1.354300 < ttable 2.01808 and a significance value of 0.1829 > 0.05. While the Earning Per Share (EPS) variable in the partial test gets a t-statistic value of 4.608657> ttable 2.01808 with a significance value of 0.0000 <0.05, so that Earning Per Share (EPS) partially affects stock prices. In the F test, the F-statistic is obtained 13.08787> ftable 3.219942 with a significance value of 0.000038 <0.05, so it is concluded that the Net Profit Margin (NPM) and Earning Per Share (EPS) variables simultaneously affect the share price of retail trade subsector companies on the Indonesia Stock Exchange (IDX).